Effects of anesthetic management on persistent pain after breast cancer surgery - Yu Sakai; Ayako Kobayashi; Mariko Akata; Kentaro Tojo; Takahiro Mihara; Akimitsu Yamada; Kazutaka Narui; Sadatoshi Sugae; Nobuyasu Suganuma; Takahisa Goto; Tomoyuki Miyazaki (PLoS ONE, 2025)
Background Persistent pain after breast cancer surgery (PPBCS) affects 20–35% of patients, significantly impacting their quality of life. Although prevention through perioperative intervention is crucial, effective strategies to prevent PPBCS have not been established. In particular, the role of anesthetic management in preventing PPBCS remains controversial. Methods This multicenter, retrospective, observational study included 183 women aged 20–70 years who underwent unilateral breast cancer surgery under general anesthesia between April 2012 and March 2014. Pain was assessed using a numerical rating scale (NRS) during follow-up visits. PPBCS was categorized as ‘no’ (NRS = 0), ‘mild’ (NRS = 1–2), and ‘moderate-to-severe’ (NRS ≥ 3) pain. Univariate and multivariate analyses evaluated associations between perioperative factors and PPBCS. Results Of 183 participants, 127 (69.4%) reported PPBCS: 59 (32.2%) mild and 68 (37.2%) moderate-to-severe. No significant associations were found between anesthetic management factors (including total intravenous anesthesia vs. volatile anesthesia, intraoperative opioid doses, and use of adjuvant analgesics) and PPBCS incidence or intensity. Axillary lymph node dissection was significantly associated with moderate-to-severe PPBCS (odds ratio: 2.04; 95% confidence interval: 1.04–4.00). Conclusion No significant associations were found between anesthetic management and PPBCS. Further research is needed to identify anesthetic factors that may prevent PPBCS.